2019
DOI: 10.3390/cancers11020174
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Glioblastoma (GBM) with the Addition of Tumor-Treating Fields (TTF): A Review

Abstract: Glioblastoma (GBM) is the most common primary brain tumor. Despite aggressive treatment, GBM almost always recurs. The current standard-of-care for treatment of newly diagnosed GBM has remained relatively unchanged since 2005: maximal safe resection followed by concomitant chemoradiation (CRT) with temozolomide (TMZ), and subsequent adjuvant TMZ. In 2011, the first-generation tumor treating fields (TTF) device, known at the time as the NovoTTF-100A System (renamed Optune), was approved by the Food and Drug Adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
137
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(156 citation statements)
references
References 32 publications
(67 reference statements)
0
137
0
Order By: Relevance
“…GBM accounts for a vast majority of malignant brain tumors in the central nervous system and has high mortality and disability rates 1 . Although aggressive treatments, such as maximal resection, adjuvant radiotherapy, and chemotherapy are used for patients with GBM, the survival rate is still difficult to improve, 15 due to the poor understanding of the pathogenesis of GBM and the lack of an effective therapeutic target. Previous studies have reported that differential genes play an important role in the pathology of tumors and may be potential therapeutic targets 16–18 .…”
Section: Discussionmentioning
confidence: 99%
“…GBM accounts for a vast majority of malignant brain tumors in the central nervous system and has high mortality and disability rates 1 . Although aggressive treatments, such as maximal resection, adjuvant radiotherapy, and chemotherapy are used for patients with GBM, the survival rate is still difficult to improve, 15 due to the poor understanding of the pathogenesis of GBM and the lack of an effective therapeutic target. Previous studies have reported that differential genes play an important role in the pathology of tumors and may be potential therapeutic targets 16–18 .…”
Section: Discussionmentioning
confidence: 99%
“…Although there is an accumulating body of evidence demonstrating enhanced efficacy of the combined treatment of TTFields and chemotherapeutic agents or radiotherapy 1,2,9,[11][12][13][14][15][16][17][18]29 , not much is known about TTFields-responsive sensitisers. Here, we report novel TTFields-responsive sensitisers, BTNPs, characterised by high dielectric constants.…”
Section: Discussionmentioning
confidence: 99%
“…Many preclinical and clinical studies indicate that TTFields would be applicable for other tumour types including breast, lung, pancreatic, and ovarian cancers 4,6,7,9,10 . Early clinical trials have shown that only TTFields treatment for GBM patients was not significantly better than conventional chemotherapy 3,9,[11][12][13] . However, recent preclinical studies suggest that combination therapy of TTFields with conventional treatments including chemotherapy, immunotherapy, and radiotherapy are more effective than TTFields monotherapy in GBM 1,2,9,[11][12][13][14][15][16][17][18] .…”
mentioning
confidence: 99%
“…This however this concept has yet to be fully investigated and may not be clinically feasible based on the requirements for medical screening tests [43]. However, the Food and Drug Administration approved in 2005 Novocure's Tumour Treatment Fields (renamed recently to Optune), which utilises alternating current across the cranium in recurrent post-surgical GBM in combination with chemotherapy [44]. As such, the use of a direct current EF to manipulate GBM cell migration has yet to be optimised for clinical use.…”
Section: Discussionmentioning
confidence: 99%